Effects of different diesel particulate filter on emission characteristics of in-use diesel vehicles. Issue 24 (17th December 2019) - Li, Jiachen; Ge, Yunshan; Wang, Haohao; Yu, Chao; Yan, Xindi; Hao, Lijun; Tan, Jianwei
ABSTRACT: With the increasingly stringent emission regulations, retrofitting in-use vehicles with matched diesel particulate filter (DPF) becomes a cost-effective measure to meet the regulations emission limit. Forty in-use heavy-duty diesel vehicles and 15 non-road diesel engines were retrofitted with DPF and the effects of DPF on the emission characteristics were investigated in this work. A high-efficiency matching method to select DPFs for different retrofitting applications has been presented in this paper. The results also verified that the particle number (PN) of all the diesel vehicles decreased over 95% after suitable matching of DPFs. It indicated that this method could be used for reference in other retrofitting projects.